Consolidation of clay slurry using vacuum preloading method - Wang, Teng Jiao. (2010)
This report is based on the Final Year Project: Consolidation of Clay Slurry using Vacuum Preloading Method. This method is usually applied on a large scale in coastal region to improve soil conditions. However, in the laboratory, it is simulated by using a cylindrical steel can, with diameter of 300 mm, an airproof cap on the top and a piston on the bottom. Totally there are seven model tests, with different clay samples (Marine Clay, Kaolin) and different treating condition (with or without surcharge and gravel layer, band-shape vertical drain or cylindrical vertical drain), each of the Model test has lasted for around 2 weeks. There are serious of soil experiments following the model tests. What involved are: initial/final water content, specific gravity, Atterberg limit, grain size distribution, ne-dimensional consolidation and UC tests. This report introduces the basic concept for both material and method, and then elaborated the experiment procedures. Results and data for all tests are shown in part 6 of the report. Part 7 is the discussion of the testing results. And Part 8 is the summary, it tells the conclusion for effect of different treating conditions on the soil samples. Part 8 is the references of this report. Appendices are attached at the end of the report. All the experiment data are listed in appendices for the use of discussion and study.